2018
DOI: 10.3899/jrheum.171218
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pregnancy on Disease Activity in Patients with Psoriatic Arthritis

Abstract: Continuation of biologics therapy was associated with a low level of disease activity and a low probability of flare during pregnancy. Stopping treatment with biologics before pregnancy is associated with flare during pregnancy and the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…A recent retrospective study found no significant change in PsA disease activity during pregnancy, but a statistically significant aggravation was observed during the postpartum period compared with the third trimester (n = 33 live births; p = .01; Berman et al, 2018). Similarly, in a prospective multicenter study including 103 women with PsA (n = 108 pregnancies) from a Norwegian nationwide register, PsA disease activity decreased during pregnancy and increased within 6 months postpartum (Ursin et al, 2018).…”
Section: Psoriasis and Pregnancymentioning
confidence: 93%
See 1 more Smart Citation
“…A recent retrospective study found no significant change in PsA disease activity during pregnancy, but a statistically significant aggravation was observed during the postpartum period compared with the third trimester (n = 33 live births; p = .01; Berman et al, 2018). Similarly, in a prospective multicenter study including 103 women with PsA (n = 108 pregnancies) from a Norwegian nationwide register, PsA disease activity decreased during pregnancy and increased within 6 months postpartum (Ursin et al, 2018).…”
Section: Psoriasis and Pregnancymentioning
confidence: 93%
“…On the other hand, discontinuation of biologic treatment before pregnancy or during the first trimester (n = 15 of 21 pregnancies) was associated with significant disease worsening during pregnancy and in the postpartum period (odds ratio: 7; 95% CI, 0.5-98.6), but no significant changes were reported in the small number of patients who continued on biologic therapy beyond the first trimester (n = 6; anti-tumor necrosis factor [anti-TNF]: n = 5; ustekinumab: n = 1; Berman et al, 2018). In line with these findings, although only a small number of women with PsA used anti-TNFs during pregnancy (n = 7) in the Norwegian study, disease activity 6 months postpartum was significantly lower in this group (mean DAS28-C-reactive protein with anti-TNF: 2.22 vs. without anti-TNF: 2.72; p = .043; Ursin et al, 2018).…”
Section: Psoriasis and Pregnancymentioning
confidence: 99%
“…There is evidence that SLE becomes more severe during pregnancy and in the postpartum period [ 9 ]. Similarly, symptoms of psoriatic arthritis (PsA) worsen as well [ 10 , 11 ]. It has been established that discontinuing effective biologic treatment before a planned pregnancy leads to exacerbation of PsA during pregnancy and puerperium.…”
Section: Autoimmune Disease and Pregnancymentioning
confidence: 99%
“…It has been established that discontinuing effective biologic treatment before a planned pregnancy leads to exacerbation of PsA during pregnancy and puerperium. Therefore Berman et al recommend considering continuing biologics during pregnancy [ 11 ].…”
Section: Autoimmune Disease and Pregnancymentioning
confidence: 99%
“…In the psoriatic arthritis cohort, the postpartum flare rate is 28-55%, and in keeping with the Norwegian (Revnatus) data, this seems to be highest at 6 months postpartum. As in the spondyloarthritis group, flare rates are associated with stopping anti-TNF early [12][13][14].…”
Section: Postpartum Flaresmentioning
confidence: 99%